Analysis of Marketing Strategies to Achieve Room Occupancy Targets with the SWOT Method at Grand Tamaro Parapat Hotel - Malau, Geby Hotmauli; Iriani, Iriani (Program Pascasarjana Magister Teknik Industri Universitas Mercu Buana, 2024)
Hotel is one of the service businesses that can support improving the tourism industry through the facilities and infrastructure provided. The marketing strategy carried out by a hotel is very influential on the success of achieving the room occupancy target set by the hotel. Grand Tamaro Hotel is one of the hotels located in a tourism city in Indonesia, namely the city of Parapat, which is experiencing a problem of decreasing room occupancy rates, where from 2020 to 2022 Grand Tamaro Hotel cannot reach the room occupancy target that has been set. This study aims to determine the marketing strategy for achieving room occupancy targets using the SWOT method at the Grand Tamaro Hotel. This research is a quantitative study using purposive sampling technique as a sampling technique. The sample in this study were visitors who had visited the Grand Tamaro Hotel at least once with a total of 80 respondents. The results of this study indicate that the position of the Grand Tamaro Hotel is in quadrant II, namely the position of the diversification strategy with an IFAS score of 3.9 and an EFAS score of 4. This position shows that the Grand Tamaro Hotel faces several threats but has internal strengths. The strategy that must be applied during this condition is to take advantage of strengths to maximize long-term opportunities. Judging from the condition of the hotel, the strategy that can be applied is the S-T strategy which utilizes strength factors to overcome the threats at the Grand Tamaro Hotel.